2010
DOI: 10.1111/j.1365-3059.2010.02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of ACC deaminase‐producing bacteria on crown gall formation in tomato plants infected by Agrobacterium tumefaciens or A. vitis

Abstract: This study showed that various rhizosphere bacteria producing the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase (ACCD), which can degrade ACC, the immediate precursor of ethylene in plants, and thereby lower plant ethylene levels, can act as promising biocontrol agents of pathogenic strains of Agrobacterium tumefaciens and A. vitis. Soaking the roots of tomato (Solanum lycopersicum) seedlings in a suspension of the ACCD-producing Pseudomonas putida UW4, Burkholderia phytofirmans PsJN or Azospirillum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Similar results have been obtained with castor bean and tomato plants infected by Agrobacterium tumefaciens. While P. putida UW4 was able to decrease crown gall formation and subsequent damage and loss of plant biomass, the acdS knockout mutant had no significant impact on protecting tomato plants from the A. tumefaciens infection (Hao et al 2007;Toklikishvili et al 2010). These results suggest that ACC deaminase activity, and the consequent lowering of deleterious plant ethylene levels, is the mechanism responsible for P. putida UW4 plant growth promotion activity as well as its ability to protect plants against biotic as well as abiotic stress (Grichko et al 2000;Wang et al 2000;Cheng et al 2007;Glick et al 2007;Hao et al 2007;Gamalero et al 2010;Toklikishvili et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results have been obtained with castor bean and tomato plants infected by Agrobacterium tumefaciens. While P. putida UW4 was able to decrease crown gall formation and subsequent damage and loss of plant biomass, the acdS knockout mutant had no significant impact on protecting tomato plants from the A. tumefaciens infection (Hao et al 2007;Toklikishvili et al 2010). These results suggest that ACC deaminase activity, and the consequent lowering of deleterious plant ethylene levels, is the mechanism responsible for P. putida UW4 plant growth promotion activity as well as its ability to protect plants against biotic as well as abiotic stress (Grichko et al 2000;Wang et al 2000;Cheng et al 2007;Glick et al 2007;Hao et al 2007;Gamalero et al 2010;Toklikishvili et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While P. putida UW4 was able to decrease crown gall formation and subsequent damage and loss of plant biomass, the acdS knockout mutant had no significant impact on protecting tomato plants from the A. tumefaciens infection (Hao et al 2007;Toklikishvili et al 2010). These results suggest that ACC deaminase activity, and the consequent lowering of deleterious plant ethylene levels, is the mechanism responsible for P. putida UW4 plant growth promotion activity as well as its ability to protect plants against biotic as well as abiotic stress (Grichko et al 2000;Wang et al 2000;Cheng et al 2007;Glick et al 2007;Hao et al 2007;Gamalero et al 2010;Toklikishvili et al 2010). In addition, it has been previously demonstrated that transgenic plants that express a bacterial acdS gene under the control of a root specific promoter are more resistant to pathogen induced stress as well as abiotic stress caused by salt, flooding and metals (Robison et al 2001a, b;Grichko and Glick 2001;Grichko et al 2000;Stearns et al 2005;Sergeeva et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, seedling inoculation with bacteria expressing ACC deaminase may reduce pathogen-induced ethylene, e.g. for soil-borne disease caused by pathogenic bacteria such as Pseudomonas syringae pv tomato (Indiragandhi et al, 2008), Agrobacterium tumefaciens (Toklikishvili et al, 2010;Hao et al, 2011), Erwinia spp. (Wang et al, 2000), and fungi, including Pythium ultimum (Wang et al, 2000), Pythium aphanidermatum (El-Tarabily, 2013), and Pyricularia oryzae (Amutharaj et al, 2012).…”
Section: Fungal and Bacterial Pathogensmentioning
confidence: 99%
“…The plant growth promoting effects of ACC deaminase may be most effective during pathogen attack [94,[170][171][172] and in stressful environments (e.g., flooded and heavy-metal contaminated soils) [173,174]. Additionally, under stress conditions plant vitamin synthesis declines.…”
Section: Modern Approaches To Agriculture Management-utilization Of Pmentioning
confidence: 99%